CARRYING CAPACITY OF EAST BEACH OF BULUKUMBA REGENCY FOR MARINE TOURISM ACTIVITIES - Andi Panca Wahyuni; . Yonvitner; Isdradjad Setyobudiandi (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2017)
The purpose of the study was to assess the carrying capacity of  East Beach of Bulukumba Regency for tourism activities. East Beach was obtained three marine tourism activities namely beach tourism of recreation, snorkeling and diving. Coastal tonamelyurism/recreation categories according to the total length area that utilized around 1.696  m can accommodate 68 people/day, snorkeling tourism around  71.605 m² can accommodate 286 people/day and diving tourism around 98.534  m²  is able to accommodate 394 people/day. Thus the total tourist that can fit to the overall tourism activity around 748 people/day. Keywords : carrying capacity, marine tourism, east beach, Bulukumba regency